2020
DOI: 10.4081/idr.2020.8743
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Hyperoxia Exposure in Suppressing Human Immunodeficiency Virus Replication: An Experimental In Vitro in Peripheral Mononuclear Blood Cells Culture

Abstract: Cellular immune has an important role in response HIV infection, which is attack the infected cells to activate signaling molecule. Hyperbaric Oxygen (HBO) worked as complementary treatment for HIV infection. The production of ROS and RNS molecules during hyperbaric exposure can affect gene expression which contributes to cellular adaptative response. This study was conducted to explore the mechanisms of cellular adaptive response to HIV infection during hyperbaric exposure. This study was carried on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Target prediction of differentially expressed genes in another murine study suggested that regulation of gene expressions of dopamine metabolism and nitric oxide synthesis were significantly affected by carbon monoxide poisoning and HBO treatment [ 3 ]. HBO exposure to in vitro HIV-1- infected cells led to several signaling processes in the cell, such as those stimulating NFκb, interferon α, and p21, all of which affect each other to inhibit HIV virus replication [ 4 ]. Human proteomic or omics studies related to prolonged hyperbaric oxygen exposure and pulmonary oxygen toxicity in humans do not exist in the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Target prediction of differentially expressed genes in another murine study suggested that regulation of gene expressions of dopamine metabolism and nitric oxide synthesis were significantly affected by carbon monoxide poisoning and HBO treatment [ 3 ]. HBO exposure to in vitro HIV-1- infected cells led to several signaling processes in the cell, such as those stimulating NFκb, interferon α, and p21, all of which affect each other to inhibit HIV virus replication [ 4 ]. Human proteomic or omics studies related to prolonged hyperbaric oxygen exposure and pulmonary oxygen toxicity in humans do not exist in the current literature.…”
Section: Introductionmentioning
confidence: 99%